IJCM_75A: Assessment of Perinatal Anxiety among Postpartum Mothers admitted in Tertiary Care Hospital, Raipur City (Chhattisgarh) - Soni Shikha; Gupta Shubhra Agrawal; Dhurandhar Tripti; Agrawal Shailendra (Wolters Kluwer Medknow Publications, 2024)
Background: Maternal mental and emotional health plays an important role in child nutrition and health. About 10% of pregnant women and 13% of women who recently gave birth suffer from perinatal depression and anxiety. This can impair maternal functioning, cause distress, and may interrupt mother-infant bond formation. Objectives: 1) To assess the Perinatal anxiety among postpartum mothers using PASS (Perinatal Anxiety Screening Scale). Methodology: This is a cross-sectional study conducted in postpartum mothers after 24 hr of delivery admitted in Tertiary Care Hospital, Raipur City (Chhattisgarh). After taking informed consent. consecutive sampling was applied for the collection of data and the sample size was 400. €¢ Perinatal anxiety-related questions asked by Perinatal anxiety screening scale which is a 4-point Likert scale (not at all/some times/often/almost always). This scale contains a total of 31 questions which are divided into 04 domains i.e. Excessive worry and specific fears, perfectionism, control and trauma, social anxiety, acute anxiety, and adjustment having 10, 08, 05, and 08 no. of questions in each domain respectively. Results: Only 14.5% of study subjects are asymptomatic while almost all ie 85.5% have varying grades of perinatal anxiety ranging from mild to moderate i.e.54.75%, and severe anxiety i.e. 30.75%. Conclusion: The new mothers are very much anxious about perfectionism, control, and trauma i.e. 91.5% have mild-moderate symptoms of anxiety severity for this domain.